2021
DOI: 10.3390/ma14216665
|View full text |Cite
|
Sign up to set email alerts
|

PBF-LB Process-Induced Regular Cavities for Lightweight AlSi10Mg Structures

Abstract: In powder bed fusion with laser beam (PBF-LB), two process-induced defects by pore formation are known: local spherical pores by the keyhole effect and geometrically undefined pores caused by lack of fusion. Both pore types are heterogeneously distributed and can be used for lightweight or damping design applications. The achievable porosity is limited to around 13%. This article presents a novel process-controlled method enabling the targeted and reproducible manufacturing of solid parts with regularly distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that the E L has an influence on the structural properties of PBF‐LB/M manufactured materials such as texture, porosity, and microstructure. [ 30,49,50 ] However, likely to the relatively narrow E L ‐range investigated here, the structural features are similar regardless to the applied E L . To further assess the impact of different microstructural states, samples were annealed, as described earlier.…”
Section: Resultsmentioning
confidence: 83%
“…Several studies have suggested that the E L has an influence on the structural properties of PBF‐LB/M manufactured materials such as texture, porosity, and microstructure. [ 30,49,50 ] However, likely to the relatively narrow E L ‐range investigated here, the structural features are similar regardless to the applied E L . To further assess the impact of different microstructural states, samples were annealed, as described earlier.…”
Section: Resultsmentioning
confidence: 83%